(untitled) (Research, Society and Development, 2022)
This article presents a look at the field educators from the action Escola da Terra, from PRONACAMPO. It was developed in the context of the subject Public Policies and Education of the Field, offered in the second semester of 2021, in the Graduate Program in Teaching of Sciences and Humanities (PPGECH) at the Federal University of Amazonas - UFAM, Humaitá Unit - IEAA. The general objective is to analyze whether the actions of the Escola da Terra have been reflected in the teaching activities of women educators in Amazonas, considering the question that drives the research: How have the actions of the Escola da Terra reflected on the teaching practice of women educators in the field in the Amazon context? We sought, then, to reflect on the pedagogical practice of women educators in Amazonas; to discuss the pedagogical training course offered by the Escola da Terra; and to understand if the feminine condition interferes in the teaching performance of women educators in the field. The theoretical and methodological support is based on the post-critical methodology in Education, based on authors who move between the prefix "Post" fields brought by Meyer and Paradise (2012), anchored in feminist and gender studies, Berth (2020) and Holland (2020). Data production was from the narrative interview, Andrade (2012) and document analysis, Ludke and André (2013). The analysis of the results was made from a qualitative approach, according to Gastaldo (2018) and suggests that the actions of the Escola da Terra did not reach the interviewed educators and are not reflected in the pedagogical practices developed. The feminine condition appeared as a significant influence on the idea of empowerment of the subjects in the process of resistance and search for an autonomous and emancipatory education.